Menakar Kepercayaan Publik Kepada Pemerintah terhadap Isu Keamanan Digital - Alma Palomita; Santi Indra Astuti (Bandung Conference Series: Communication Management, 2023)
Abstract. Digital Security Issues are a problem that often befalls Indonesia. As a result, the level of public trust that the community has in the government is decreasing every year. Moreover, since the emergence of the Bjorka hacker case in the mass media. The purpose of this study is to find out how the level of public trust in the government is owned by Members of the Student Executive Board of the Faculty of Communication Sciences, Bandung Islamic University. The research method used is quantitative descriptive analysis. The sample of this research is Student Members of the Student Executive Board of the Faculty of Communication Sciences, Bandung Islamic University, which has 66 members. The results of the study concluded that public trust held by BEM members of the Faculty of Communication Sciences, Bandung Islamic University was also influential due to the news about the Bjorka hacker case. From the first to the last aspect of public trust, namely the aspects of cognition, affection and behavior. All category values are in low equivalent or have low public trust. This is an important capital for the Government in improving digital security. Abstrak. Isu Keamanan Digital merupakan masalah yang seringkali menimpa Indonesia. Dampaknya, tingkat kepercayaan publik yang dimiliki masyarakat kepada pemerintah semakin menurun setiap tahunnya. Apalagi, semenjak munculnya kasus hacker Bjorka di media massa. Tujuan dari penelitian ini ialah untuk mengetahui bagaimana tingkat kepercayaan publik kepada pemerintah yang dimiliki Anggota Badan Eksekutif Mahasiswa Fakultas Ilmu Komunikasi Universitas Islam Bandung. Metode penelitian yang digunakan adalah analisis deskriptif kuantitatif. Sampel dari penelitian ini ialah Mahasiswa Anggota Badan Eksekutif Mahasiswa Fakultas Ilmu Komunikasi Universitas Islam Bandung yang beranggotakan 66 orang. Hasil penelitian menyimpulkan bahwa kepercayaan publik yang dimiliki anggota BEM Fakultas Ilmu Komunikasi Universitas Islam Bandung juga berpengaruh akibat adanya pemberitaan mengenai kasus hacker Bjorka. Dari aspek kepercayaan publik pertama hingga terakhir yaitu aspek kognisi, afeksi dan perilaku. Nilai kategori seluruhnya ada dalam ekuivalen rendah atau memiliki kepercayaan publik yang rendah. Ini menjadi modal penting bagi Pemerintah dalam meningkatkan keamanan digital.